2009
DOI: 10.1007/s10840-009-9449-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy is effective even in elderly patients with comorbidities

Abstract: Purpose The purpose of this study was to compare the effects of cardiac resynchronization therapy (CRT) in elderly patients (≥65 years) with younger patients and to assess the impact of comorbidities in CRT remodeling response. Methods This is a prospective study of 87 consecutive patients scheduled for CRT who underwent clinical and echocardiographic evaluation before and 6 months after CRT. A reduction in left ventricular end-systolic volume (LVESV) ≥15% after CRT defined remodeling responders, and a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
(36 reference statements)
2
11
0
6
Order By: Relevance
“…Although baseline NYHA and LVEF were similar between the two age groups, a higher proportion of younger recipients had NICM. Older patients are more likely to receive CRT‐P alone than in combination with a defibrillator . This may be associated with preference for improving quality of life rather than providing lifesaving shocks in older patients with HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although baseline NYHA and LVEF were similar between the two age groups, a higher proportion of younger recipients had NICM. Older patients are more likely to receive CRT‐P alone than in combination with a defibrillator . This may be associated with preference for improving quality of life rather than providing lifesaving shocks in older patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients are more likely to receive CRT-P alone than in combination with a defibrillator. 5,6 This may be associated with preference for improving quality of life rather than providing lifesaving shocks in older patients with HF. Alternatively, CRT-P may improve LVEF, such that ICD placement may not be indicated.…”
Section: Characteristics Of Older Crt Recipientsmentioning
confidence: 99%
“…However, no randomized controlled trials have addressed the value of CRT in elderly HF patients [22][23][24][25][26]. Elderly HF patients (≥75 years) have been underrepresented or excluded in the aforementioned CRT trials despite the fact that HF is more prevalent in the very elderly as compared with younger patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that renal impairment does not prevent the positive response to CRT, even in elderly patients [19]. Actually, previous studies have indicated that CRT can be a renal-protective strategy in HF and that the improvement in renal function can be another mechanism to explain the beneficial effects of CRT [20][21][22].…”
Section: Impact Of Comorbiditiesmentioning
confidence: 99%
“…In addition, diabetes is a powerful independent predictor of morbidity and mortality among patients with HF [24]. Regarding the impact of diabetes on CRT effectiveness, previous studies have demonstrated that this frequent comorbidity is not a predictor of poor response [19,25]. In fact, diabetic HF patients treated with CRT seem to have a very favorable functional and survival outcome, which is comparable to non-diabetic patients [26].…”
Section: Impact Of Comorbiditiesmentioning
confidence: 99%